2019
DOI: 10.1155/2019/1609717
|View full text |Cite
|
Sign up to set email alerts
|

Six-Year Real-World Outcomes of Antivascular Endothelial Growth Factor Monotherapy and Combination Therapy for Various Subtypes of Polypoidal Choroidal Vasculopathy

Abstract: The purpose of this study was to compare 6-year visual outcomes of antivascular endothelial growth factor (anti-VEGF) monotherapy and initial combination therapy of photodynamic therapy (PDT) and anti-VEGF therapy for polypoidal choroidal vasculopathy (PCV) in a Chinese population and to investigate imaging biomarkers associated with visual outcomes. Forty-eight treatment-naive PCV eyes of 46 patients were reviewed retrospectively, which underwent anti-VEGF monotherapy or initial combination therapy. PCV was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
3
2
0
Order By: Relevance
“…The deterioration of visual acuity at the end of five years was significantly more in eyes with poor baseline vision <o.60 log MAR (<0.001) and type 1 PCV compared to type 2(<0.001). Our results were similar to another study by Jingyuan Yang et al 5 who also reported a better outcome in type 2 PCV at 1 year.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The deterioration of visual acuity at the end of five years was significantly more in eyes with poor baseline vision <o.60 log MAR (<0.001) and type 1 PCV compared to type 2(<0.001). Our results were similar to another study by Jingyuan Yang et al 5 who also reported a better outcome in type 2 PCV at 1 year.…”
Section: Discussionsupporting
confidence: 92%
“…Long-term outcomes of various management options in real world have been reported. 5 Our present study aims to know the biomarkers predicting the long-term outcomes of PCV in Indian population and evaluate various factors that correlate with better visual outcomes in PCV patients.…”
Section: Introductionmentioning
confidence: 99%
“…Of the risk factors for good first-dose anatomical response to anti-VEGF therapy in non-pachy-PCV patients, higher CMT reflects retinal edema, morphological abnormalities in the PED indicate the activeness of the PL, and a high percentage of IRF possibly indicates that anti-VEGF drugs promote the alleviation of macular edema. Previous studies showed that other OCT features, such as PED height [20], SFCT [21,22], and continuous RPE [23], are potential risk factors for the anti-VEGF response to PCV, which was partially consistent with our study. During follow-up of patients, CMT showed a significant decrease from baseline at all periods of follow-up (V1-V6) in the good first-dose anatomical response group, whereas the poor first-dose anatomical response group showed significant improvements at only a few periods.…”
Section: Discussionsupporting
confidence: 92%
“…Of the risk factors for good first-dose anatomical response to anti-VEGF therapy in non-pachy-PCV patients, higher CMT reflects retinal edema, morphological abnormalities in the PED indicate the activeness of the PL, and a high percentage of IRF possibly indicates that anti-VEGF drugs promote the alleviation of macular edema. Previous studies showed that other OCT features, such as PED height [20], SFCT [21, 22], and continuous RPE [23], are potential risk factors for the anti-VEGF response to PCV, which was partially consistent with our study.…”
Section: Discussionsupporting
confidence: 92%
“…For anti-VEGF monotherapy, the PLANET study showed good visual and functional response in > 85% of treated patients, with few number of patients requiring adjunct PDT. In a real-world study, anti-VEGF monotherapy and combination therapy had comparable long-term visual outcomes after a follow-up of 6 years 36 . Another study reported comparable visual outcome, but fewer intravitreal injections and longer time of recurrence in the combination group 31 .…”
Section: Discussionmentioning
confidence: 94%